Comportamiento agronómico del cultivo del nabo (brassica rapa ssp pekinensis) con diferentes abonos orgánicos en el Centro Experimental La Playita del cantón La Mana, año 2014 - Macías Espinal, Benito Leonardo (2015)
During the research agronomic performance turnip (Brassica rapa ssp pekinensis) with different levels of organic fertilizers that developed in the Experimental Center of Canton La Playita La Manna it was pursued objectives are to evaluate the level of organic fertilizer that affects the agronomic performance of turnip ; establish the best level of organic fertilizer and perform economic analysis for this 150 m2 were used in plots 2 meters long and 1 meter wide, fertilizers were the humus and water hyacinth with levels of 1, 3 to 5 kg m2. The statistical design used was a completely randomized design (DBCA) blocks, variables were evaluated: emergency percentage, percentage of seizure, plant height, leaf number, length and width of leaves, stem diameter and weight and performance the plot. To develop research and analysis of soil macro nutrients, micro soil microbiological and water were made. For the length and width of leaf at 15 and 30 days reported the highest value in treating 5 kg of humus m2 with 14,13 and 31,61cm and in the days to harvest the highest value was in 3 kg m2 32.99 cm humus, the same happened to the sheet width of 6.38, 15.78 cm for 15 to 30 days and 14.59 cm at harvest time for the treatments described above, the largest number leaf harvest treatment I reported 5 kg of humus with 25.58 m2. The greater weight per plant was registered in 1kg water hyacinth with 542.75 m2 while the highest yield per plot I attribute to treatment 5 kg of humus m2 with 6.60 kg, the highest benefit / cost ratios were obtained with 1kg water hyacinth treatments per m2 and 5 kg of humus m2 with 2.95 and 1.33